Pelaksanaan Mediasi oleh Kantor Agraria Tata Ruang/Badan Pertanahan Nasional Kabupaten Boyolali Dalam Penyelesaian Sengketa Waris - Ratna Sari Pratiwi; Nanik Sutarni; Muhammad Fauzan Hidayat (Fakultas Hukum Universitas Boyolali, 2021)
Acquired land questions that are not as per clear arrangements, bringing about irreconcilable circumstances between families. This is known as a